(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this paper, we proposed a mathematical model for monkey pox disease dynamics. This model is divided into two sub-population which is a system of non-linear differential equations. It is made up of seven (7) compartments such as the Susceptible, the Infectious, the Treatment, the Recovery, the Susceptible, the Infectious, and the Recovery (SITR-SIR). The model is formulated with the aid of a schematic diagram using appropriate parameters. The model analysis was carried out to show the feasible region, the disease-free equilibrium points, the basic reproduction number, and the local stability of the model. The model was solved to show the effect of the parameters.